Sekolah Ramah Anak Era Revolusi Industri 4.0 Di SD Muhammadiyah Pajangan 2 Berbah Yogyakarta - Ahmad Tarmizi Hasibuan; Rahmawati Rahmawati (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2019)
The era of industrial revolution 4.0 is known as the era of openness that calls for the quality of human resources characterized by technological capabilities. Sophisticated technology results in a decrease in character for adults, including educators. Based on research from several regions in Indonesia conducted by UNICEF (2006), it was proved that around 80% were still prone to violence in the school environment conducted by educators to students. Based on the case above, the writer wants to give advice by creating child-friendly schools that are able to provide children's rights in order to be able to provide pleasant and comfortable services. This research was conducted at the Muhammadiyah Elementary School 2 in Berbah Yogyakarta. This research is a qualitative research that uses a phenomenological approach. In collecting data using the trianggulation method and reading related books. Based on the results of research to realize child-friendly schools in the industrial revolution era 4.0, SD Muhammadiyah Pajangan 2 Berbah applied. 6M, namely: 1) Cultivating 5S (greetings, smiles, greetings, courtesy and courtesy), 2) instilling Muhammadiyah pledges, 3) improving habituation (Riyadhoh), 4) improving infrastructure, 5) improving the quality of educators, and 6) terminating School canteen.